A Research Study about the Role of Performative Language Teaching on the Understanding of Chinese Idioms - Corderi Novoa, Modesto (Sinología hispánica. China Studies Review, 2026)
Chengyu are essential to Chinese language and culture. They condense ancient Chinese wisdom in a story of four characters and are usually challenging for international students. In this research, a mixed method employing quantitative and qualitative techniques is adopted to investigate how using drama to perform the stories associated with the Chengyu might boost students’ understanding of them. The research was conducted at the language school in La Coruña, Spain, with 20 students aged 14-60, thirteen females and seven males of A1/HSK1 Chinese language level. The control and experimental groups comprised ten students who had to learn the same five Chengyu. One week after they learned the Chengyu, both groups took the same test to evaluate the degree of understanding of the five Chengyu. Statistical results show that students in the experimental group outperformed the ones in the control group. Therefore, we may argue that drama significantly helped students understand Chengyu.